Letters Home - Mekas, Jonas 1922-2019; Mekas, Adolfas 1925-2011 (Post scriptum. Littera, 2021)
This beautiful and mysterious book whose unedited pages contain a collection of letters that the famous brothers Jonas and Adolfas Mekas sent from America to Semeniškiai village, Biržai district, Lithuanian Soviet Socialist Republic. They were all addressed to the most important addressee of their lives - their mother, Elzbieta Mekienė